Factors Declining Interest in English Language Training for Sermo Tourism Village Community, Kulon Progo Yogyakarta - Nuharani Kurniyati (Media Wisata, 2022)
This study investigates the elements that contribute to the community's waning interest in English language training conducted by the "Bule Mengajar" Community in Sermo Tourism Village, Hargowilis, Kulon Progo. A qualitative method using a descriptive approach was adopted. Situations, objects, or social phenomena are described when conducting qualitative descriptive research. Apart from observations and other supporting materials, informants become a source for acquiring data through organized interviews with trainers and training participants. When it comes to data veracity, triangulation is applied. Data gathering, data reduction, display, and conclusions were all part of the interactive analysis. According to research, the Sermo Tourism Village community's lack of interest in English training is attributable to a lack of proper training.